New Black and African Writing: Volume 2 - Emezue, Gloria Monica T.; Smith, Charles (Book collections on Project MUSE., 2015)
New black and African writing Vol. 2 is our concluding edition of a series that has featured many critical entries and reviews on canonical African fiction, poetry, drama and non-fiction. This second edition explores intricacies of relationships and associations, the recurrent tropes for the interpretation and understanding of historical connections, and the shaping of thought brought into fictional and cultural renditions that are evolving and continually reassessed although around the periphery of older canons. The quest for a meaningful heuristic for approaching contemporary arts is almost totally redefined by the contributions of eminent scholars of our time whose balancing and correspondence create room for complementarity of values and toward cultural understanding and value appreciation in contemporary society.